2018
DOI: 10.4103/0973-1482.172717
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of 30 patients with bone marrow metastases

Abstract: To make primary origin clear and start systemic antitumor therapy is beneficial for patients with bone marrow metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 12 publications
2
10
0
Order By: Relevance
“…Fever without chills was mostly Grades 0–1, accounting for 94.0% of cases. These findings were consistent with those of previous reports 3–6,8–10 . The results of the current study showed that patients with BMM generally had low‐grade fever without chills and normal WBC counts, and those with leukopenia only had a small probability of BMM.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Fever without chills was mostly Grades 0–1, accounting for 94.0% of cases. These findings were consistent with those of previous reports 3–6,8–10 . The results of the current study showed that patients with BMM generally had low‐grade fever without chills and normal WBC counts, and those with leukopenia only had a small probability of BMM.…”
Section: Discussionsupporting
confidence: 93%
“…The findings of the current study are consistent with those of previous reports 8,9 . BMM often has no obvious symptoms, unless it causes severe fever, anemia, or bleeding 3–6,8–10 . BC with BMM is not common in clinical practice, and many clinical doctors do not have a clear or comprehensive understanding of the disease.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The most frequent cause of chronic hyponatremia in cancer patients is SIAD, mainly due to ectopic vasopressin secretion by cancer cells [ 50 , 51 , 52 , 53 ]. Several clinical evidences reported hyponatremia as an independent, negative prognostic factor in different types of blood and solid tumors (e.g., lymphoma [ 54 ], gastrointestinal cancers [ 55 , 56 ], hepatocellular carcinoma [ 57 , 58 ], mesothelioma [ 59 ], renal cell carcinoma [ 60 , 61 ], and small cell lung cancer [ 62 , 63 ]), and a concordant improvement of overall and progression-free survival after the appropriate correction of reduced serum [Na + ] [ 24 ], even in patients with extensive and terminal disease [ 64 ]. Accordingly, hyponatremia has been proposed as a biomarker able to identify high-risk subjects affected by lung cancer [ 65 ].…”
Section: Hyponatremia and Healthmentioning
confidence: 99%
“…It is now widely accepted that hyponatremia represents a negative independent prognostic factor in oncologic patients, and is associated with poor progression-free and overall survival in several cancers [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ]. The direct contribution of this electrolyte imbalance (which cannot be considered a mere surrogate marker of the severity of clinical conditions) is supported by the observation that the correction of serum [Na + ] may reduce the overall mortality rate in hyponatremic patients [ 37 ].…”
Section: Non Osmotically-induced Oxidative Stressmentioning
confidence: 99%